The Analysis of Arterial Stiffness in Heart Failure Patients in Comparison with Healthy Subjects and Patients with Cardiovascular Risk Factors - Feola, Mauro; Testa, Marzia; Ferreri, Cinzia; Rosso, GianLuca; Rossi, Arianna; Ruocco, Gaetano (Journal of clinical medicine, 2019)
The arterial stiffness in the pathogenesis and clinical outcome in heart failure (HF) patients still needs to be clarified. An increased pulse wave velocity (PWV) in HF patients in comparison with healthy subjects and cardiovascular risk factors (CVRF) patients has been demonstrated. The aim of this study was to evaluate the arterial stiffness in HF patients in comparison to control populations. Methods: Consecutive patients admitted for decompensated heart failure underwent echocardiogram and evaluation of arterial stiffness by measuring the PWV and the augmentation index (AIx75). The arterial stiffness was also calculated in a control group formed by healthy volunteers and in CVRF subjects. Results: Fifty-nine HF patients (62% males; age 75 years) with mean left ventricular ejection fraction (LVEF) 38% and N-terminal pro B-type natriuretic peptide (NT-proBNP) (8111 pg/mL) entered the study. The HF population were compared with 22 healthy controls (age 58 years) and 20 CVRF patients (age 72 years). The analysis of PWV demonstrated a velocity of 10.6 m/s (9–12.1 m/s), 11.7 m/second (10.4–12.8 m/s), and 10.1 m/second (8.6–10.8m/s) in controls, CVRF, and HF patients (p = 0.01). AIx75 was seen to be higher in the CVRF group vs. HF patients (34% vs. 22%, p = 0.001). In HF patients PWV was inversely correlated with the glomerular filtration rate (r = –0.40; p = 0.002) and directly with central systolic pressure (SP) (r = 0.29; p = 0.02), brachial SP (r = 0.33; p = 0.01) as well as AIx75 correlated with GFR (r = −033; p = 0.01). Conclusion: PWV proved to be different in HF patients in comparison with CVRF/healthy population. The strongest correlation was revealed between the values of PWV/AIx75 and renal function.